PENGARUH PENGATURAN KEMAMPUAN AWAL DENGAN CTL TERHADAP HASIL BELAJAR FISIKA DASAR I MAHASISWA JURUSAN FISIKA FMIPA UNIMED - Jurubahasa Sinuraya (LPPM Universitas Negeri Medan, 2012)
This study aims to determine whether there is a significant difference learning outcomes Physics I among freshmen group that got the initial setup through the application of the principle of CTL and student groups who did not receive initial capacity setting in the Department of Physics Science Faculty Unimed. The design includes quasi-experimental study. This study population is students of Department of Physics. Using sampling techniques class (cluster sampling), sample of a population is represented by two classes, one class as the experimental class and the class as a control class. Instruments of this study is to test the learning outcomes. Hypothesis testing used two-sided t test. The data analyzed were derived from the normal distribution and homogeneous population. Based on the data analysis and discussion, the findings of this study it can be concluded that: there is a significant difference in learning outcomes between the Basic Physics I freshmen who received the original settings through the application of the principle of CTL and the group of students who did not receive initial capacity setting in the Department of Physics Science Faculty Unimed .